Effect of mixing on the sequence structure of molecular chain and properties of copolyurea. Issue 22 (18th February 2022) - Gao, Zhangcheng; Feng, Lianfang; Gu, Xueping; Duan, Jintang; Zhang, Cailiang
Abstract: Copolyureas have a variety of sequence structures because of the diversity of monomer types and quantities, which directly determine their properties. 4, 4′‐diphenylmethane diisocyanate (MDI), m‐phenylenediamine (MPD), and polyoxypropylenediamine (D2000) are used as monomers to study the influence of mixing on the sequence structure of as‐prepared copolyurea. D2000 as a macromolecular aliphatic diamine has an extremely high reactivity with MDI, which is two to three orders of magnitude higher than that of MPD with MDI. While the molecular chain of D2000 is much longer than that of MPD, resulting in that the reaction between D2000 and MDI is much easier to change from reaction control to diffusion control than that between MPD and MDI. It is verified that the enhanced mixing can dramatically reduce the hindered effect of diffusion, and promote the reaction of MDI and D2000 to change the sequence structure of as‐synthesized copolyurea. Specifically, as the stirring speed increased from 100 to 800 rpm, the content of MPD‐MDI‐MPD segment decreased from 57 to 15 mol%, while that of MPD‐MDI‐D2000 and D2000‐MDI‐D2000 segments increased from 39 and 4 mol% to 64 and 21 mol%, respectively. As a result, the as‐synthesized copolyureas become more ductile from the high tensile strength and hardness. More specifically, the Shore A hardness, tensile strength, and the broken elongation of the as‐synthesized copolyureas were changed from 81, 56 MPa and 65% to 68, 40 MPa and 188%, respectively. Abstract : Adjustment of copolyurea sequence structure and properties by changing stirring speed